A research synthesis on successful educational practices and student outcomes for physical education in schools - He, Juan; Yu, Hongli; Jiang, Man; Bialas, Marcin (Frontiers in Psychology, 2023)
Although successful educational practices (SEPs) in higher education institutions have wellestablished student outcomes, the vast majority do not meet physical education standards in schools. Despite the promising nature of policy initiatives supporting schools, there is scant evidence of how these SEPs affect student outcomes. This review aimed to determine the status of the literature and the type of evidence regarding school SEPs. Several studies have demonstrated that these SEPs contribute directly or indirectly to improving student outcomes. Three objectives were examined and synthesized in our review of SEP research findings. The first goal is to identify different types of impacts on students in schools. The second goal is to provide educators, principals, and policymakers with a unified and comprehensive framework. Lastly, we provide suggestions for future SEP research. The review identified 45 studies that met our inclusion criteria. Our reviewed studies documented impacts on the individual level. It encompasses both students' instrumental abilities and their sense of self-esteem and motivation. Secondly, improving interpersonal relationships, reducing conflict, and increasing group cohesion are important components at the group level. Finally, there are factors at the community level, including absenteeism reduction, parental involvement, and changes in attitudes towards school. Current research supports the effectiveness of successful school practices. It stresses the importance of implementing policies to maximize student outcomes. Finally, the review concludes by discussing findings implications and future research directions.